ANTARA MERUSAK DAN MEMANFAATKAN HUTAN MANGROVE PADA MASYARAKAT PESISIR (Studi Etnosains pada Hutan âBakauâ di Masyarakat Pesisir Desa Pematang Pasir, Lampung) - Ardianto, Wawang; Rochana, Erna (JURNAL SOSIOLOGI, 2013)
Mangrove is groups of plants growing along the coast and mangrove has a high adaptation ability to salinity of brackish water where it has to live in this environment. Mangrove forest functions to protect mainland from sea water abrasion, to provide living for people, to be environment for sea fish breeding. People have their reasons for inhabiting and using mangrove forest; not only for mangrove potential, but also their social background to live there. People control to mangrove forest is conducted by processes and from one season to another. People are aware of what they are doing as destructing mangrove forest. However, they do not have other options because their family members need food and their children have to go to school. Stopping mangrove forest destruction can be done by means of some stages. First, people should be aware of environment potentials when it is in good and destructed conditions, second village government should be consistent about their job descriptions and coordinate with its people to preserve environment, and finally, the Forestry Office should be routinely monitoring mangrove forest register.